Effect of Mulch Type on Onion Plant Growth and Production (Allium ascalonicum L. - Reza Pahlevi; Rosmaiti Rosmaiti; Yenni Marnita (University of Prof. Dr. Hazairin, SH, 2023)
This study aims to determine the effect of mulch use on the growth and production of onion plants (Allium ascalonicum L.) This study used (RAK) non-factorial 9 levels, M0 = Control, M1 = Bagasse, M2 = Palm Shells, M3 = Rice Sacks, M4 = Reeds M5 = MPHP, M6 = Coconut Husk, M7 = Sawdust, M8 = Rice Husks. Parameters in the study were plant height (cm), number of leaves, wet weight of tubers/samples (g), wet weight of tubers/plots (g), and number of tubers/samples (cloves). The results of the study had a very noticeable effect on plant height (cm) aged 42 HST had a real effect on those aged 35 HST, and an unreal effect on the age of 7, 14, 21, and 28 HST. The best results were obtained in the treatment of the use of M3 mulch, the mulch treatment had a very noticeable effect on the number of leaves at the age of 7, 14, 28, 35, and 42 HST, an unreal effect on the age of 21 HST. Observations of the wet weight of tubers per sample, per plot (g), and the number of tubers per sample had an unreal effect.